2020
DOI: 10.1016/j.cub.2020.01.045
|View full text |Cite|
|
Sign up to set email alerts
|

Spatial Comparisons of Mechanosensory Information Govern the Grooming Sequence in Drosophila

Abstract: SUMMARY Animals integrate information from different sensory modalities, body parts, and time points to inform behavioral choice, but the relevant sensory comparisons and the underlying neural circuits are still largely unknown. We use the grooming behavior of Drosophila melanogaster as a model to investigate the sensory comparisons that govern a motor sequence. Flies perform grooming movements spontaneously, but when covered with dust, they clean their bodies following an ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(56 citation statements)
references
References 53 publications
3
53
0
Order By: Relevance
“…dust) and mechanical displacements of the antennae ( Hampel et al, 2015 ; Phillis et al, 1993 ; Seeds et al, 2014 ). Moreover, neuronal silencing experiments have linked the JO-C/E neurons to the grooming response to dust and the JO-F neurons to the grooming response to antennal displacement: Zhang et al, 2020 recently reported that dust-elicited grooming could be disrupted by expression of tetanus toxin using a driver line that appears to target the JO-C/E neurons, while we previously found that expression of tetanus toxin in JO-F neurons (using aJO-spGAL4-1) disrupted the grooming response to displacements of the antennae ( Hampel et al, 2015 ). These studies suggest that the JON subpopulations detect these different mechanical stimuli and initiate the grooming response.…”
Section: Discussionmentioning
confidence: 99%
“…dust) and mechanical displacements of the antennae ( Hampel et al, 2015 ; Phillis et al, 1993 ; Seeds et al, 2014 ). Moreover, neuronal silencing experiments have linked the JO-C/E neurons to the grooming response to dust and the JO-F neurons to the grooming response to antennal displacement: Zhang et al, 2020 recently reported that dust-elicited grooming could be disrupted by expression of tetanus toxin using a driver line that appears to target the JO-C/E neurons, while we previously found that expression of tetanus toxin in JO-F neurons (using aJO-spGAL4-1) disrupted the grooming response to displacements of the antennae ( Hampel et al, 2015 ). These studies suggest that the JON subpopulations detect these different mechanical stimuli and initiate the grooming response.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the JO-CE neurons are implicated in the grooming response to dust, while the JO-F neurons are implicated in the response to antennal displacements. A recent study showed that expression of tetanus toxin (TNT) using a driver line that appears to target JO-CE neurons disrupted dust induced grooming (Zhang et al, 2020). We found that expression of TNT using a driver that mostly targets the JO-F neurons (aJO-spGAL4-1) disrupted the grooming response to displacements of the antennae (Hampel et al, 2015).…”
Section: Diverse Jon Subpopulations Converge Onto the Antennal Commanmentioning
confidence: 79%
“…We previously demonstrated that this manipulation induces grooming, beginning with the anterior body parts, and alternating between bouts of head cleaning and front leg rubbing (Hampel, McKellar, Simpson, & Seeds, 2017; Zhang, Guo, & Simpson, 2020). Here, we combine optogenetic activation for constant sensory input with temperature control to show that both individual leg movements and bout-level alternations increase in a correlated manner.…”
Section: Resultsmentioning
confidence: 99%